Climate change and long-term human behaviour in the Neotropics: an archaeological view from the Global South - Scheinsohn, Vivian Gabriela (2023)
In this paper, we argue for the inclusion of archaeology in discussions about how humans havecontributed to and dealt with climate change, especially in the long term. We suggest NicheConstruction Theory as a suitable framework to that end. In order to take into account both humanand environmental variability, we also advocate for a situated perspective that includes the GlobalSouth as a source of knowledge production, and the Neotropics as a relevant case study to consider.To illustrate this, we review the Mid-Holocene Hypsithermal period in southern Puna and continentalPatagonia, in southern South America, by assessing the challenges posed by this climate period andthe archaeological signatures of the time from a Niche Construction Theory perspective. Finally, weemphasise the importance of these considerations for policymaking.